2013
DOI: 10.1179/1607845413y.0000000086
|View full text |Cite
|
Sign up to set email alerts
|

Quality of harvest and role of cell dose in unrelated bone marrow transplantation: An Italian Bone Marrow Donor Registry–Gruppo Italiano Trapianto di Midollo Osseo Study

Abstract: In this study, we investigated the factors affecting cell dose harvest and the role of cell dose on outcome. We analysed data from a cohort of 703 patients who underwent unrelated bone marrow transplantation facilitated by IBMDR in GITMO centers between 2002 and 2008. The median-infused cell doses is 3.7 × 10(8)/kg, the correlation between the nucleated cells requested from transplant centers and those harvested by collection centers was adequate. A harvested/requested cells ratio lower than 0.5 was observed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The methodology of the bone marrow harvest is critical for the outcome of patients undergoing the transplantation. The higher number of nucleated cell dose and CD34+ cell dose influences the outcome of the transplantation and is generally associated with better outcome . The studies however do not show one threshold of bone marrow cell dose which is optimal for transplant what might be in part explained by different methodologies and possibly higher rates of graft vs leukemia effect and graft‐vs‐host disease after transplants with grafts with higher CD34+ and CD3+ cell content …”
Section: Introductionsupporting
confidence: 52%
“…The methodology of the bone marrow harvest is critical for the outcome of patients undergoing the transplantation. The higher number of nucleated cell dose and CD34+ cell dose influences the outcome of the transplantation and is generally associated with better outcome . The studies however do not show one threshold of bone marrow cell dose which is optimal for transplant what might be in part explained by different methodologies and possibly higher rates of graft vs leukemia effect and graft‐vs‐host disease after transplants with grafts with higher CD34+ and CD3+ cell content …”
Section: Introductionsupporting
confidence: 52%
“…The recent combined adult and pediatric Italian study included one hundred and sixteen patients with nonmalignant disease, and TNC dose did exhibit a positive relationship between increased TNC cell dose and both overall survival and event‐free survival . Our study included fifteen patients with nonmalignant disease and sample size precluded a separate subset analysis for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of these studies, however, included pediatric patients with nonmalignant diseases . More recently, a combined adult and pediatric Italian study noted that higher cell doses led to improved outcomes for recipients with nonmalignant diseases and lower cell doses led to higher relapse risks in recipients with early malignant diseases …”
Section: Discussionmentioning
confidence: 99%
“…In addition, specific technical aspects of the BM collection, which differ from center to center, may have a profound influence on the TNC concentrations collected. For example, the speed of the collection and harvest draws can impact the concentration collected, with faster collections yielding lower TNC concentrations [14,18]. The speed of collection can be influenced both by harvester technique and the type of needle used in the collection [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the speed of the collection and harvest draws can impact the concentration collected, with faster collections yielding lower TNC concentrations [14,18]. The speed of collection can be influenced both by harvester technique and the type of needle used in the collection [18,19]. In addition, some studies have suggested that large-volume collections and longer collection times can decrease the likelihood of obtaining the desired TNC dose [20,21].…”
Section: Discussionmentioning
confidence: 99%